Effect of compaction pressure on microstructure and densification of alumina-titania composite prepared by powder metallurgy route - Siti Nursyuhada Yahaya (2017)
In this study, the effect of milling time and compaction pressure on the densification and morphology of Al2O3-TiO2 composite was evaluated. The composite was produces using powder metallurgy route via low energy ball milling and cold compaction. The milling time and compaction pressure was varied at 15, 30, 45 and 60 h and 200, 400, 600 and 800MPa, respectively. The result showed as milling time increased, will produce homogeneous morphology, decrease crystallite size and increased internal strain of Al2O3-TiO2 composite powder. No new phase was formed even at longer milling time (60 h). The densification of Al2O3- TiO2 composite also enhanced with increasing compaction pressure. It was found that the optimum milling time and compaction pressure was during 60 h and at 800 MPa, respectively.